Spread of tetracycline resistance genes at a conventional dairy farm - Kyselková, Martina; Jirout, Jiří; Vrchotová, Naděžda; Schmitt, Heike; Elhottová, Dana (Frontiers in Microbiology, 2015)
The use of antibiotics in animal husbandry contributes to the worldwide problem of increasing antibiotic resistance in animal and human pathogens. Intensive animal production is considered an important source of antibiotic resistance genes released to the environment, while the contribution of smaller farms remains to be evaluated. Here we monitor the spread of tetracycline resistance (TC-r) genes at a middle-size conventional dairy farm, where chlortetracycline (CTC, as intrauterine suppository) is prophylactically used after each calving. Our study has shown that animals at the farm acquired the TC-r genes in their early age (1-2 weeks), likely due to colonization with TC-resistant bacteria from their mothers and/or the farm environment. The relative abundance of the TC-r genes tet(W), tet(Q) and tet(M) in fresh excrements of calves was about 1-2 orders of magnitude higher compared to heifers and dairy cows, possibly due to the presence of antibiotic residues in milk fed to calves. The occurrence and abundance of TC-r genes in fresh excrements of heifers and adult cows remained unaffected by intrauterine CTC applications, with tet(O), tet(Q) and tet(W) representing a ‘core TC-resistome’ of the farm, and tet(A), tet(M), tet(Y) and tet(X) occurring occasionally. The genes tet(A), tet(M), tet(Y) and tet(X) were shown to be respectively harbored by Shigella, Lactobacillus and Clostridium, Acinetobacter, and Wautersiella. Soil in the farm proximity, as well as field soil to which manure from the farm was applied, was contaminated with TC-r genes occurring in the farm, and some of the TC-r genes persisted in the field over 3 months following the manure application. Concluding, our study shows that antibiotic resistance genes may be a stable part of the intestinal metagenome of cattle even if antibiotics are not used for growth stimulation, and that smaller dairy farms may also contribute to environmental pollution with antibiotic resistance genes.